2010
DOI: 10.1007/s12603-010-0052-7
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders in aging and dementia

Abstract: This paper reviews the characteristics of sleep disorders found in people at a greater risk of dementia: the elderly adult, patients with mild cognitive impairment (MCI) and those with neurodegenerative diseases. The frequency of sleep architecture modifications and circadian rhythm sleep disturbances increases with age. Although around 40% of older adults complain of poor sleep, true sleep disorders are far less prevalent in healthy older adults and are frequently associated with comorbidities. The sleep diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
129
1
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(148 citation statements)
references
References 50 publications
(51 reference statements)
5
129
1
8
Order By: Relevance
“…It has been proposed that chronic sleep deprivation and associated neuronal overactivity may directly confer an increased risk of developing AD [26] . Sleep disturbance is more frequent in patients with AD than the general population [36] , occurring in some 25-54% of patients overall [54,58] ; as this is based largely on caregiver reports, it may be an underestimate. Sleep disturbance occurs early in the course of disease [61] and worsens as disease evolves [27,69] , though not necessarily in a simple monotonic relation [39,63] .…”
Section: Evidence For the Hypothesis: Sleep Alterations In Admentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that chronic sleep deprivation and associated neuronal overactivity may directly confer an increased risk of developing AD [26] . Sleep disturbance is more frequent in patients with AD than the general population [36] , occurring in some 25-54% of patients overall [54,58] ; as this is based largely on caregiver reports, it may be an underestimate. Sleep disturbance occurs early in the course of disease [61] and worsens as disease evolves [27,69] , though not necessarily in a simple monotonic relation [39,63] .…”
Section: Evidence For the Hypothesis: Sleep Alterations In Admentioning
confidence: 99%
“…However, converging evidence drawn from molecular biology, sleep neuroscience [21][22][23][24][25][26][27][28][29][30][31][32][33][34] and clinical neurology [35][36][37][38][39][40][41][42] suggests that sleep may interact in diverse and important ways with the pathophysiology of AD. Ramifications of long-term disruption in the sleep-wake cycle could include synaptic overactivity and excitotoxicity [10,21,[43][44][45] , impaired synaptic pruning [46] , failure of synaptic scaling and homeostatic responses [19,20,27,[47][48][49][50][51] , transmission of pathogenic proteins (β-amyloid and tau) [9,15,16] , and disruption of neural circuitry in the vulnerable DMN [6,8,12,21,52,53] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the three cited reviews in this issue confirmed that our knowledge in the field of sleep disorders in older adults and in dementia has increased in recent years (4)(5)(6). The challenges of coming decades will be to optimize the understanding of the role of sleep in the cognitive process and its potential implication at earlier stages and in presence of particular behaviors in AD.…”
mentioning
confidence: 94%
“…Bombois and their colleagues published a comprehensive review on the association between dementia and sleep disorders including insomnia (mainly secondary to medical, psychosocial comorbidities or multiple medications), daytime sleepiness, rapid eye movement (REM) sleep behaviour disorder, sundowning, restless legs syndrome, periodic leg movements and sleep-disordered breathing (4). Etiologies of sleep disturbances in patients with AD is thought to be multifactorial and include components specific to dementia and a number of nonspecific factors associated with the normal aging process.…”
mentioning
confidence: 99%
“…Bright light (2000 lux) given in the morning can reverse this abnormality and can reduce agitated behavior (63). Sleeping abnormalities, especially sleep apnea, have been associated with rapid cognitive decline (64,65).…”
mentioning
confidence: 99%